(untitled) (Comprehensive Journal of Science, 2025)
This study aims to explore the extent to which digital transformation contributes to the development of accounting systems and its impact on improving the quality of financial reporting at Jumhouria Bank – Oil Research Agency. This comes in light of global trends toward digitizing financial and accounting operations, and the increasing demand for accurate and transparent financial reports that support governance and accountability requirements. The study seeks to achieve several objectives, most notably: identifying the impact of digital transformation on the development of accounting systems within the bank; evaluating its effect on the quality of financial reporting; measuring the relationship between the development of accounting systems using digital technologies and the improvement in the quality of financial reports; and proposing recommendations to enhance the use of digital transformation in accounting systems to produce high-quality financial reports. The descriptive analytical method was adopted, and the questionnaire was distributed to employees in the financial management and internal audit departments, as they are directly involved in applying accounting systems and preparing financial reports. A total of 30 questionnaires were distributed, of which 25 were returned and deemed valid for analysis, with a response rate of 83.3%. The study findings revealed that digital transformation has a direct and positive impact on the development of accounting systems in the bank, contributing to improved operational efficiency and accuracy of financial information. It also showed that digital transformation plays a key role in enhancing the quality of financial reporting through improved transparency, reliability, and speed of access to information. The study concluded with a set of recommendations, most notably the need to develop the bank’s technological infrastructure and invest in training and qualifying human resources in the field of digital transformation, in order to enhance financial performance quality and enable the bank to keep pace with digital changes and achieve excellence in the modern banking environment.